Implementation of Ibnu Khaldun's Thoughts in Islamic Education in the Era of Society 5.0: Holistic and Contextual Approach - Aristya, Septian; Atmaja, Bondan Tri; Deraputra, Ahmad Abid; Dewi, Dita Yovieta (STMIK Widya Cipta Dharma, 2024)
Humans were created by Allah SWT as servants (abd) and leaders (khalifah fil ardh), requiring them to base every action on knowledge. The importance of knowledge is emphasized in the Al-Qur'an (QS. At-Taubah: 122) and the hadith of the Prophet SAW, highlighting it as a necessity in all aspects of life. In the era of Society 5.0—a human-centered society integrating the virtual and physical worlds—education plays a crucial role in developing technological capabilities while maintaining morality and character. One solution to this challenge is the application of Ibnu Khaldun's educational philosophy, which emphasizes education as a means of transferring knowledge, building character, and fostering morality. This research employs a pure library research method using a descriptive analytical approach. The study aims to examine the implementation of Ibnu Khaldun's educational concepts in addressing the challenges of the Society 5.0 era. With a holistic and contextual approach, the research envisions Islamic education that is both adaptive and relevant. The implications include developing a holistic curriculum that integrates intellectual, moral, and spiritual values; fostering responsiveness to social and technological changes by updating curricula and learning methods; emphasizing practical skills through innovative approaches such as project-based learning; and enhancing teacher competencies through pedagogical and technological training. In conclusion, Ibnu Khaldun's educational philosophy provides a strong foundation for Islamic education in the Society 5.0 era. It aims to create a generation that is not only technologically competent but also deeply rooted in Islamic values, cultivating individuals who are morally upright, wise, and prepared to face global challenges.